2016
DOI: 10.1016/j.solener.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Design, analysis and performance of a polymer–carbon nanotubes based economic solar collector

Abstract: A low cost flat plate solar collector was developed by using polymeric components as opposed to metal and glass components of traditional flat plate solar collectors. In order to improve the thermal and optical properties of the polymer absorber of the solar collector, Carbon Nanotubes (CNT) were added as a filler. The solar collector was designed as a multi-layer construction with an emphasis on low manufacturing costs. Through the mathematical heat transfer analysis, the thermal performance of the collector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fluoropolymers: The most promising class of polymers, usually use as film thin for collector glazing in spite of their high price, they have excellent UV resistance and stability and sufficient tear resistance [18] On the other hand absorber materials must have high thermal resistance for a long time and, good as well as fixed mechanical properties during work but the major requirements in absorber material is high thermal conductivity. Polymer has a conductivity in range of 0.1 to 0.5 W/m.K [20]. This obstacle can overcome by increasing absorber area.…”
Section: Polyphenylene Ether Polystyrene Blend and Polyethylenementioning
confidence: 99%
“…Fluoropolymers: The most promising class of polymers, usually use as film thin for collector glazing in spite of their high price, they have excellent UV resistance and stability and sufficient tear resistance [18] On the other hand absorber materials must have high thermal resistance for a long time and, good as well as fixed mechanical properties during work but the major requirements in absorber material is high thermal conductivity. Polymer has a conductivity in range of 0.1 to 0.5 W/m.K [20]. This obstacle can overcome by increasing absorber area.…”
Section: Polyphenylene Ether Polystyrene Blend and Polyethylenementioning
confidence: 99%
“…Moreover, the flexibility of polymer materials presents opportunities for technological advancement by addressing these weaknesses. Table 4 summarizes the research exploring the use of polymer materials in PVT systems [103][104][105][106][107][108][109][110][111][112]. Yandri [103] conducted a study analyzing the thermal energy produced by a current passing through conduction materials in a PVT system, utilizing a combination of polymethyl methacrylate (PMMA) and a copper sheet to construct the absorber.…”
Section: Degradation Main Factormentioning
confidence: 99%
“…Comparisons with other studies utilizing different polymer materials revealed similar findings. Kim et al [110] modified absorber materials to polycarbonate to reduce costs while optimizing heat transfer by adding filler to the polymer layer. Their initial design, which included carbon nanotubes (CNTs) as filler, effectively improved the solar collector's thermal performance.…”
Section: Degradation Main Factormentioning
confidence: 99%
“…The time and cost could however be much reduced in a mass production context using a formed or extruded base plate with continuous, automated welding or using an alternative manufacturing technique, for instance roll-bonding [28,29]. For non-evacuated solar collectors, micro-channel absorbers could also be produced cheaply using injection-moulded polymers [30,31]: the low material conductivity necessitates a micro-channel or flooded design instead of a serpentine tube. Polymers were not considered for this project because they are currently unsuitable for high-vacuum, high-temperature use.…”
Section: Experimental Fabrication Of a Micro-channel Platementioning
confidence: 99%